Carnot battery: Simulation and design of a reversible heat pump-organic Rankine cycle pilot plant - Eppinger, Bernd; Steger, Daniel; Regensburger, Christoph; Karl, Jürgen; Schlücker, Eberhard; Will, Stefan (Applied Energy, 2021)
Keywords: Process simulation; PTES; CAD; Carnot battery; Reversible heat pump – organic Rankine cycle

COMBINING AN ORGANIC RANKINE CYCLE AND A HEAT PUMPCYCLE IN A TEST PLANT FOR REVERSIBLE STORAGE OFENERGY - Steger, Daniel; Regensburger, Christoph; Eppinger, Bernd; Will, Stefan; Karl, Jürgen; Schlücker, Eberhard (Proceedings of the 5th International Seminar on ORC Power Systems, 2019)
The heat pump cycle is a well-known concept to lift the temperature of a medium by using electricalenergy and waste heat. The ORC-process on the other side offers the possibility to obtain electricalenergy from thermal energy. Combining these two processes and adding a thermal storage enables aninnovative and reversible energy storage concept calledCombined Heat Pump - Organic Rankine Cycle(HP-ORC). This paper describes preliminary considerations, design methods and the development of aHP-ORC-pilot-plant. The upper and lower storage temperature are critical factors, as they determine thestorage capacity and influence the overall efficiency (power-to-power-efficiency). Methods of multi-criteria decision-making, such as Pareto-Optimization, identify favorable combinations. The selectionof the working fluid has also a strong impact on the combined process, as apparatus properties alter, insome cases effecting significant increase in costs. The realization of the compressor of the heat pumpandtheexpanderoftheORCinonesinglemachineisanothercomplextasktobeconsidered. Especiallythe lubrication system has to fulfill the demands of both modes, thus innovative designs of the oil supplyand separation are show

Computational aeroacoustic simulations of small vertical axis wind turbine - Weber, Johannes; Regensburger, Christoph; Tautz, Matthias; Becker, Stefan; Hüppe, Andreas; Kaltenbacher, Manfred (45th International Congress and Exposition on Noise Control Engineering: Towards a Quieter Future, INTER-NOISE 2016, 2016)
Reducing the noise of wind turbines, which are installed in the vicinity of urban areas, is one major issue for social acceptance. In general, horizontal wind turbines are the most common configuration for using wind energy. However, the interest of small wind turbines are grown in the last years because of the future demand for decentralized power generation. The present work deals with two different numerical schemes of noise prediction of small vertical axis wind turbines using hybrid methods. For both schemes the time-dependent turbulent flow field is solved with Scale-Adaptive Simulation. The two schemes then differ in how the location of the acoustic sources and their propagation is calculated. In the first scheme the Ffowcs-Williams Hawkings method is used which is based on a free field Green's function. The far field acoustic radiation is calculated by extrapolation of the acoustic waves. In the second scheme the acoustic source terms are computed according to Perturbed Convective Wave Equations, which gives source terms located on the original CFD grid. These source terms are projected onto a coarser acoustic grid on which the propagation is calculated by solving the wave equation. Both methodologies are compared with each other and validated with experimental data.
Keywords: Noise; Simulation; Wind turbines

Design aspects of a reversible heat pump - Organic rankine cycle pilot plant for energy storage - Steger, Daniel; Regensburger, Christoph; Eppinger, Bernd; Will, Stefan; Karl, Jürgen; Schlücker, Eberhard (Energy, 2020)
Combining a heat pump cycle (HP) and an organic Rankine cycle (ORC) in one reversible cycle and adding a thermal storage enables an innovative and reversible energy storage concept. This paper describes preliminary considerations, design methods and the development of a HP-ORC-pilot-plant. The storage temperatures are critical factors, as they determine the storage capacity and influence the power-to-power-efficiency. Methods of multicriteria decision-making, such as Pareto optimization, identify favorable combinations. On this basis a pilot plant is designed for 90°C lower and 120°C upper storage temperature aiming at a power-to-power-efficiency of 59% and an electrical storage capacity of 3,6 kWh/t. The selection of the working fluid has also a strong impact on the reversible process, as apparatus properties alter, in some cases effecting significant increase in costs. In the considered case the refrigerant R1233zd(E) shows the best combination of performance, costs and safety. The realization of the compressor of the heat pump and the expander of the organic Rankine cycle in one single machine is another complex task to be considered. Especially the lubrication system has to fulfill the demands of both modes, thus innovative designs of the oil supply and separation are shown, like parallel and serial layouts.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Carnot battery; Heat pump; ORC; Pareto optimization; PTES; Reversible machine

Heat Exchangers in Carnot Batteries: Condensation and Evaporation in a Reversible Device - Steger, Daniel; Regensburger, Christoph; Pham, Vu Jenny; Schlücker, Eberhard (Energies, 2021)
The combined heat pump-organic Rankine cycle is a thermal-electrical storage concept which allows the reversible use of components in both operation modes (loading and unloading the storage). This saves in terms of investment costs but also creates challenges during design and operation. A heat exchanger is an expensive component destined to be used for the reversible purposes of a heat pump condenser and an organic Rankine cycle evaporator. In this study, the operation of such an apparatus was evaluated based on an analytical model, experimental data and thermal imaging. This study shows that the model can predict the filling of the apparatus distinguished by liquid, vapour and the two-phase region. The thermal imaging supports the model and gives the location of the regions. Connecting both methods, a valid statement about the current condition of the heat exchanger is possible. Due to very small pinch points, the apparatus is not efficiently used in the investigated modes. Extending the pinch to 2 K can already save up to 46.1% of the heat exchange area. The quality of the heat transfer in the evaporator (qORC = 10.9 kW/m(2)) is clearly higher than in the condenser (qHP = 6.1 kW/m(2)).
CRIS-Team WoS Importer:2021-10-08

Modular two-phase heat storage for Carnot Batteries - Regensburger, Christoph; Steger, Daniel; Schlücker, Eberhard (Energy Proceedings, 2020)
Carnot Batteries are a promising approach to store electrical energy in a thermal way. Besides the loading and unloading thermodynamic processes, the heat storage is a field of mayor interest in research. This paper presents an innovative modular storage setup that is easily scalable and contains an immiscible liquid phase to separate the hot and cold side of a sensible water storage. The separation of hot and cold side thus reduces the heat losses and improves the efficiency of the whole storage concept. A pilot plant to study the idea experimentally is in construction.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Carnot Battery; modular energy storage; sensible heat storage; thermal stratification; two-phase

Planung einer regenerativen Wärmepumpen-ORC-Anlage - Steger, Daniel; Regensburger, Christoph; Schlücker, Eberhard (Jahrestreffen der ProcessNet-Fachgruppe Energieverfahrenstechnik, 2019)

Reversible heat pump-organic rankine cycle systems for the storage of renewable electricity - Staub, Sebastian; Bazan, Peter; Braimakis, Konstantinos; Müller, Dominik; Regensburger, Christoph; Scharrer, Daniel; Schmitt, Bernd; Steger, Daniel; German, Reinhard; Karellas, Sotirios; Pruckner, Marco; Schlücker, Eberhard; et al. (Energies, 2018)
Keywords: Heat pump; Heat storage; Efficiency; Electricity storage; Organic Rankine Cycle